PENDAMPINGAN DAN PENGUATAN KAPASITAS PENGURUS KELOMPOK LANSIA DI PERUM BUMI ASRI DADAPREJO MALANG (STAI Darul Qalam Tangerang, 2022)
The partner of this community service program is the administrator of the rw 9 elderly group Bumi Housing Asri Dadaprejo. Based on interviews with the Chairman's Mother RW 9, the Chairman of the Elderly Group, and the Treasurer of the Elderly Group, several obstacles were found, among others; Management exists but vacuum approximately 3 (three) years. This is due to the busyness of administrators in managing external activities in a social-community context. Thus, elderly activities in RW 9 are more likely to be absent; 2) The elderly group in RW 9 has actually been formed. Unfortunately, there is minimal participation. As for some who are active, they only follow the Elderly Posyandu and the Independent Elderly Program; 3) There is a longing and strong desire of the administrator to activate activities in his own environment so as to motivate togetherness and active participation in the RW 9 environment. This anxiety refers to the experience of 3 (three) years ago of elderly management where almost all were excited in participating in activities held in rw 9. Based on the analysis of the situation and problems faced by the elderly group management, the implementation team submitted a solution in the form of